2015
DOI: 10.1089/sur.2014.023
|View full text |Cite
|
Sign up to set email alerts
|

Bactibilia and Antibiotic Resistance in Elective Cholecysctectomy: An Updated Ecologic Survey

Abstract: Although the influence of bactibilia in developing surgical complications is limited, its composition and the high rate of resistance can be influential enough to modify antibiotic treatment in biliary tract infections, especially in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In the present study, there was no correlation between bactobilia and postoperative infectious complications, which is in agreement with some other studies (6,7,12,17). On the contrary, some studies have reported a higher incidence of postoperative infectious complications in patients in where bactobilia was detected, especially when cholecystectomy is performed in patients with complicated gallstone disease (13).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, there was no correlation between bactobilia and postoperative infectious complications, which is in agreement with some other studies (6,7,12,17). On the contrary, some studies have reported a higher incidence of postoperative infectious complications in patients in where bactobilia was detected, especially when cholecystectomy is performed in patients with complicated gallstone disease (13).…”
Section: Discussionsupporting
confidence: 92%
“…In one patient, we isolated acinetobacter the risk factor, and the possibility of this type of contamination related to the hospital, and it is not expected to be isolated from healthy non-hospitalized patients. It was shown recently that prolonged bile duct obstruction leads to an impaired intestinal wall barrier and as a result, bacteria can colonize bile easier, thus, it is not surprising that gramnegative enteric bacteria, especially E. coli, are the most common bacteria causing bactobilia in many studies including ours (13)(14)(15)(16)(17)(18). In our study, imipenem and aminoglycosides, especially amikacin, were the most effective antibiotics.…”
Section: Discussionmentioning
confidence: 81%
“…7,23 However, CBD stones can cause biliary stasis, which is associated with higher rates of bactibilia (bacterial colonization of bile) compared with symptomatic cholelithiasis. 24,25 Additional factors connected to bactibilia include acute cholecystitis, intraoperative gallbladder rupture, immunosuppression, and older than 70 years. 26 These variables are also known risk factors for postoperative SSIs, 7,24,27 yet bactibilia has not been shown to be a risk factor for the development of SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Additional factors connected to bactibilia include acute cholecystitis, intraoperative gallbladder rupture, immunosuppression, and older than 70 years. 26 These variables are also known risk factors for postoperative SSIs, 7,24,27 yet bactibilia has not been shown to be a risk factor for the development of SSIs. 24,25 Although we found no difference in postoperative sepsis or SSIs, we did observe a longer hospital LOS among patients receiving a prolonged course of perioperative antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation